The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/3010548
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Released from CaSR‐Stimulated PMNs Reduce Ischaemia/Reperfusion Injury

Abstract: Ischemia-reperfusion (I/R) injury caused by acute myocardial infarction (AMI) can initiate a strong inflammatory response. Polymorphonuclear cells (PMNs) are the most important inflammatory cells. Our previous studies found that the calcium-sensing receptor (CaSR) regulates the proinflammatory effects of PMNs. However, the role and mechanism of CaSR-regulated PMNs in I/R injury remain uncertain. A rat AMI model was developed in this study and showed that the expression of CaSR on PMNs increased in AMI; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In vivo experiments showed that after intravenous injection of CaSR-PMN-exos via the tail vein in rats, the area of myocardial infarction and MDA secretion were significantly reduced, the SOD levels were increased, and cardiac function was improved. These results suggest that CaSR-PMN-exosomal lncRNA 39868 upregulates the protein PDGFD, regulates these effects through the AKT pathway, and reduces MIRI ( 55 ).…”
Section: Myocardial Ischemia-reperfusion Injurymentioning
confidence: 87%
“…In vivo experiments showed that after intravenous injection of CaSR-PMN-exos via the tail vein in rats, the area of myocardial infarction and MDA secretion were significantly reduced, the SOD levels were increased, and cardiac function was improved. These results suggest that CaSR-PMN-exosomal lncRNA 39868 upregulates the protein PDGFD, regulates these effects through the AKT pathway, and reduces MIRI ( 55 ).…”
Section: Myocardial Ischemia-reperfusion Injurymentioning
confidence: 87%
“…To investigated the mechanism of acupuncture against MI injury from a more comprehensive perspective, we studied the transcriptome from the aspects of differential genes, alternative splicing, and new genes by full-length transcriptome. In previous studies on MI, Second-generation sequencing technology (SGS) has been widely used [11,23,40,48]. However, the shortread RNA-seq method of SGS is limited to identify and quantify complex transcript isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphonuclear neutrophils (PMNs) are very important inflammatory cells. Recent study reported that exosomal lncRNA ENSRNOT00000039868 (lncRNA 39868) mediated the communications between PMNs and I/R CMs 52 . The calcium‐sensing receptor (CaSR) was found to be significantly upregulated in rat peripheral blood PMNs in acute MI and I/R CMs model in vitro 52 .…”
Section: Cms As Recipient Cells Of Exosomal Lncrnasmentioning
confidence: 99%
“…Recent study reported that exosomal lncRNA ENSRNOT00000039868 (lncRNA 39868) mediated the communications between PMNs and I/R CMs 52 . The calcium‐sensing receptor (CaSR) was found to be significantly upregulated in rat peripheral blood PMNs in acute MI and I/R CMs model in vitro 52 . CIN PMNs (CaSR activated) decreased Bax (proapoptotic protein) levels while increased Bcl‐xl levels.…”
Section: Cms As Recipient Cells Of Exosomal Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation